FORMULASI STRATEGI HOTEL UNTUK MENGHADAPI BERLAKUNYA PASAR BEBAS ASEAN - Agung Nurmansyah (Universitas Sahid Surakarta, 2015)
The level of competition in Surakarta bebepa increased sharply in recent years. Increased competition led to a change in strategy to face the competition. Because assumptions when companies determine and establish strategies that long ago turned into the assumptions in determining the new corporate strategy. To change the strategy of the things to consider in five competitive forces is the threat of entry of newcomers, the level of rivalry among existing competitors, the strength of the bargaining power of buyers, bargaining power of suppliers and the last level is the level of competition in the industry. Moreover, in 2015 the enactment of the MEA will make the competitive landscape in the Surakarta growing again.